2019
DOI: 10.1002/ase.1859
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Dissection Affects Student Performance on Gross Anatomy Practical and Written Examinations: Results of a Four‐Year Comparative Study

Abstract: The role of human dissection in modern medical curricula has been a topic of intense debate. In part, this is because dissection can be time‐consuming and curricular hours are being monitored more carefully. This has led some to question the efficacy and importance of dissection as a teaching method. While this topic has received considerable attention in the literature, the question of how dissection impacts learning has been difficult to evaluate in a real‐world, high‐stakes setting since participation in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…However, previous studies have shown a very minimal difference in scores between students practicing dissection and those who learned anatomy by using prosections and anatomical models though learning from dissected cadavers is the satisfactory method of study. Recent studies show that students favor prosections and models than using cadavers, and some anatomists believe that prosections can replace full-body dissection in coming years especially in those institutions that have adopted an integrated curriculum and PBL as a teachinglearning method and this may be attributed to limited time for practicing dissection [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown a very minimal difference in scores between students practicing dissection and those who learned anatomy by using prosections and anatomical models though learning from dissected cadavers is the satisfactory method of study. Recent studies show that students favor prosections and models than using cadavers, and some anatomists believe that prosections can replace full-body dissection in coming years especially in those institutions that have adopted an integrated curriculum and PBL as a teachinglearning method and this may be attributed to limited time for practicing dissection [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Cadaveric dissection has been, and still remains, a central tenet of gross anatomy and medical education (Pabst, 2009;Böckers et al, 2010;Hildebrandt, 2010;McBride and Drake, 2018;Thompson and Marshall, 2020). Recent studies indicate that medical students both want and expect to dissect the human body as a part of their educational experience (Gregory and Cole, 2002;Johnson, 2002;Mintz, 2016;Pais et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The development of integrated medical curriculum has increased from 61% in 2010-2011 to 76% in 2013-2014, further fragmenting the laboratory experience (Drake et al, 2014;Mintz, 2016;McBride and Drake, 2018). Studies indicate that elimination of gross anatomy dissection from the curriculum results in diminished student learning and runs counter to student preference (Rizzolo and Stewart, 2006;Pais et al, 2017;Thompson and Marshall, 2020). As a result, medical schools that had initially eliminated gross dissection have reinstated it as a part of their current curricula (Mintz, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][14][15][16][17] Despite the evidence that a cadaveric dissection-based approach offers superior understanding of clinically-relevant anatomy and surgical techniques, the depth and duration of teaching anatomical content is in decline. 2,4,14,18,19 This trend is of immense concern as it is likely to increase the gap between anatomical dissection skills required during the initial years of veterinary curriculum and the surgical skills required in an operating room in the clinical years. 1,2,4 Such gaps between the preclinical and clinical years may be unnecessary barriers in facilitating vertical integration in the veterinary curriculum.…”
Section: Introductionmentioning
confidence: 99%